(untitled) (GEOMATE Journal, 2023)
This paper aims to propose a methodology to interpret electrical resistivity tomography (ERT) in an andesitic volcanic context and to feed hydrogeological conceptual model of the structure of the aquifers in volcanic context. The study takes place in Pandaan, in the northeastern part of Arjuno Welirang volcano, Indonesia. The district relies on the groundwater supply to sustain its needs (industries, agriculture, domestics). Therefore, characterizing the aquifers boundaries and functioning is important to apply sustainable groundwater management. The methodology is in two steps, first geological and hydrogeological mapping, leading to the ERT location identifications. And second, interpretation of electrical resistivity tomography profiles with the subsurface hydrogeological dataset. In this paper, the relationships between volcanic facies and aquifer properties are well described through 15 ERT profiles, calibrated with geological outcrops, borehole logs, and hydrogeological data. The geophysical signature shows that, in the proximal–medial zone of the Arjuno Welirang volcano, major springs are located where the lava flows end (lava tip) and are in contact with a clayey layer/lahars. In the medial zone, below and above the clayey/lahars layer, the volcanic sandstone and tuff breccia respectively support unconfined and confined aquifers, with the evidence of artesian boreholes for the latter and dug wells for the former. These results lead to an improved hydrogeological conceptual model for this research area.